Factors Explaining the Performance of Entrepreneurs in the Industry 4.0: A Theoretical Approach - Tuty Sariwulan; Suparno Suparno (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2020)
This research aims to develop prepositions about entrepreneur performance in small and medium enterprises (SMEs) in the Industry 4.0 through a theoretical study approach. This paper elaborates several findings from previous studies as references and explores the grounded theory of human resource development. A qualitative research method with literature studies was conducted to obtain research reference models in explaining the factors influencing the performance of entrepreneurs in the SMEs industry. This study also provides support for the development of factors in measuring performance and the variables that affect employers’ performance. This study suggests that work skills, digital literacy, and economic literacy are the crucial reference in the development of small and medium enterprises in the fourth industrial era. Small and medium enterprises training is a national program to improve welfare because it is an indicator of economic growth. However, there are very few performance evaluations and ongoing development programs.